2015
DOI: 10.1111/cei.12632
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between serum thymic stromal lymphopoietin and anti-citrullinated peptide antibodies in patients with rheumatoid arthritis

Abstract: Summary Thymic stromal lymphopoietin (TSLP) has been suggested recently to play an important role in the pathophysiology of rheumatoid arthritis (RA). However, there is little information on serum TSLP concentrations in RA and its clinical significance. The present study investigated whether serum TSLP concentrations were affected in patients with RA. Using an enzyme‐linked immunosorbent assay (ELISA), we measured TSLP concentrations in the serum obtained from 100 patients with RA, 60 patients with osteoarthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…TNF-α stimulation of synovial cells from rheumatoid arthritis patients induces expression of TSLP, and the blood concentration of TSLP in rheumatoid arthritis patients is elevated compared with the concentration in patients with an osteoarthritic knee. 22,23 In a subsequent study, 9 we found that TSLP was highly expressed in surgical samples of patients with disc herniation, and that the supernatants of TSLP-activated mouse intervertebral disc cultures had the capacity to induce macrophage migration in an MCP-1-dependent manner in vitro. 9 It will be of great importance in the field of orthopedics to elucidate how TSLP is involved in inflammatory mechanisms in osteochondral tissue.…”
Section: Roles For Tslp In Disc Degeneration and Spontaneous Herniamentioning
confidence: 89%
See 3 more Smart Citations
“…TNF-α stimulation of synovial cells from rheumatoid arthritis patients induces expression of TSLP, and the blood concentration of TSLP in rheumatoid arthritis patients is elevated compared with the concentration in patients with an osteoarthritic knee. 22,23 In a subsequent study, 9 we found that TSLP was highly expressed in surgical samples of patients with disc herniation, and that the supernatants of TSLP-activated mouse intervertebral disc cultures had the capacity to induce macrophage migration in an MCP-1-dependent manner in vitro. 9 It will be of great importance in the field of orthopedics to elucidate how TSLP is involved in inflammatory mechanisms in osteochondral tissue.…”
Section: Roles For Tslp In Disc Degeneration and Spontaneous Herniamentioning
confidence: 89%
“…21 Its potential as a therapeutic target is being actively pursued. 21 TSLPs are produced by epithelial cells in response to exogenous stimuli such as allergens and microbial infections, 22,23 upon which immunocompetent cells such as dendritic cells, mast cells, and eosinophils are activated through activation of TSLP receptors. 24 TSLP is highly expressed in diseased tissues of patients with allergic diseases such as asthma and atopic dermatitis, and analysis using genetically modified mice revealed that the action of TSLP is required to produce antigen-specific allergic conditions.…”
Section: Failure Of Immune Tolerance and Tslpmentioning
confidence: 99%
See 2 more Smart Citations
“…Hatori K, Terakado A, Izawa N: Effectiveness of interdisciplinary team conference to manage skeletal related events in rehabilitation for patients with cancer: Juntendo Medical Journal, 2015; 61: 426-436. 13…”
mentioning
confidence: 99%